Association between Neuron-Specific Enolase Gene Polymorphism and Delayed Encephalopathy after Acute Carbon Monoxide Poisoning. (15th October 2020) - Xu, Linlin; Liu, Xuejiao; Zhao, Jing; Zeng, Jiao; Gu, Jiapeng; Zhang, Xiaoli; Zhang, Fan; Han, Yongkai; Li, Wenqiang; Zhang, Ping; Gu, Renjun
Abstract : Objective . The aim of this study is to explore the relationship between neuron-specific enolase (NSE) gene polymorphism and delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) and provide a theoretical basis for DEACMP pathogenesis, diagnosis, and prognosis. Methods . To investigate this relationship, we screened 6 NSE single nucleotide polymorphisms (SNPs), based on the results of the previous genome-wide association studies (GWAS). A total of 1, 201 patients, including 416 in the DEACMP group and 785 in the acute carbon monoxide poisoning (ACMP) group, were detected by the Sequenom MassARRAY® method. The genotype frequencies and alleles of the 6 NSE SNPs (rs2071074, rs2071417, rs2071419, rs11064464, rs11064465, and rs3213434) were compared using different genetic models. Results . In the SNPs rs2071419 and rs3213434, we found that the genotypes and allele frequencies in the two groups significantly correlated with the grouping of patients (χ 2 = 6.596, p = 0.037 ; χ 2 = 8.769, p = 0.012 ). The haplotypes GGTTTC and CCTTTC of ACMP and DEACMP were different (χ 2 = 6.563, p = 0.010 ; χ 2 = 4.151, p = 0.042 ). We also observed that rs2071419 and rs3213434 significantly correlated with DEACMP-increased risk in the dominant, codominant, and overdominant genetic models. In addition, we speculated that the C allele of the rs2071419 polymorphism and the T allele of the rs3213434 polymorphism in NSE may increase the DEACMP risk (p = 0.011, p = 0.006 ). Conclusions . The results show that rs2071419 and rs3213434 are susceptible sites of DEACMP. The NSE C allele of rs2071419 and T allele of rs3213434 and the haplotypes GGTTTC and CCTTTC may be risk factors for DEACMP.